Becoming American : why immigration is good for our nation's future - Ghadar, Fariborz (Rowman and Littlefield, 2014)
For policy makers, business leaders, and American citizens, immigration reform is one of the defining issues of this era. In turns both personal and analytical, remaining factual and well-argued throughout, Fariborz Ghadar's Becoming American makes the case for common sense immigration policies and practices that will not only help strengthen America's fledgling economy and role as world leader, but will also help millions of prospective immigrants and their families start making more out of their lives today, and for generations to come.